Features and complexity of treatment of BRCA-associated ovarian cancer, chronic disease: literature review - T. V. Gorodnova; A. P. Sokolenko; Kh. B. Kotiv; I. V. Berlev; E. N. Imyanitov (Опухоли женской репродуктивной системы, 2024)
We analyzed literature data on the peculiarities of the clinical manifestation and therapeutic approaches ofB RCA-associated ovarian carcinomas. The ESMO-ESGO consensus emphasised the importance of determining BRCA1/2 status in ovarian cancer patients for planning the entire treatment strategy. BRCA-associated carcinomas differ significantly from sporadic forms in terms of clinical course, response to systemic therapy, spectrum of drugs which are used for treatment, mechanisms of chemoresistance development, and prognosis. This category of patients needs new therapeutic approaches, including the development of tactics to overcome chemoresistance and modification of the entire combined treatment programme.